Integrated NiO2-catalyzed reforming of Sesamum indicum stalk for hydrogen-enriched producer gas and dual-fuel CI engine performance evaluation - Subramanian, Sudagar; Thamizhvel, R.; Ashokan, Anbuchezian; Rajendran, Silambarasan; Venkatesan, Elumalai Perumal; Alwetaishi, Mamdooh; Hussain, Fayaz; Keçebaş, Ali (Elsevier, 2026)
The present study develops a unified experimental framework integrating biomass gasification, NiO2-based catalytic reforming, and dual-fuel engine testing to produce and utilize hydrogen-enriched producer gas derived from Sesamum indicum (sesame) stalks. While prior studies have independently explored gasification, catalytic upgrading, or engine combustion, no previous work has experimentally coupled these domains within a single closed-loop system. In this research, a fixed-bed downdraft gasifier equipped with a NiO2-impregnated catalytic reformer was designed to generate hydrogen-rich producer gas at flowrates of 2 and 4 L/min, achieving an H2 concentration of 39.5 vol% and a calorific value of 6.4 MJ/Nm3. The integration of NiO2 catalysis enhanced hydrogen yield by 113 % and increased gas heating value by 25.5 % compared with the non-catalytic case. Engine performance evaluation under dual-fuel operation demonstrated that 2 L/min hydrogen-enriched gas with diesel achieved the highest brake thermal efficiency (29.8 %) and the lowest specific fuel consumption (0.249 kg/kWh). Emission analysis revealed reductions of 44 % in CO and 35 % in HC, with a minor 1.5 % increase in NOx due to higher adiabatic temperatures. Combustion diagnostics confirmed a 20.8 % rise in peak cylinder pressure (74.46 bar) and a 10.6 % reduction in ignition delay (10.1°CA). The study fills a critical research gap by demonstrating a NiO2-catalyzed biomass-to-engine hydrogen pathway, thereby establishing a scalable model for decentralized power generation and sustainable hydrogen utilization from agricultural residues.